PERANAN DEFERENSIASI, IT-PERFORMANCE, BUDAYA ORGANISASI DAN INOVASI TERHADAP SUSTAINABLE COMPETITIVE ADVANTAGE (SCA) Studi Empiris Perum Pegadaian Syari’ah se-Malang Raya (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
The problem of this research is the development of pawning institution. It seems slowly developed and hardly to compete with other pawning institutions. Therefore, some factors causing this problem are needed to be understood. Against this problem, the author feels necessary to examine some factors with important effect on syariah pawning, such as differentiation, IT-Performance, organizational culture, and innovation. Research type is explanatory research, in which it explains the causal relationship between research variables through hypothesis testing. Population of research is manager with authority of strategic decision making in the syariah pawning institution in Malang City. Sample is taken by census technique. Data will be subjected to Multiple Regression Analysis. Result of research indicates that Differentiation, IT-Performance, Organizational Culture, and Innovation infuence sustainable competitive advantage. It may be concluded that higher level of Differentiation, IT-Performance, Organizational Culture, and Innovation in the pawning institution can produce higher sustainable competitive advantage for pawning institutions in Malang.Keywords: IT-Performance, Organizational Culture Sustainable, SCA